2000
DOI: 10.1093/oxfordjournals.bja.a013599
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria following anaphylaxis with general anaesthesia

Abstract: Microalbuminuria is increasingly recognized as a marker of pathologies that cause acute systemic capillary leak. We report a case of an anaphylactic reaction to general anaesthesia involving cardiac arrest. In this case the urinary excretion of albumin following resuscitation suggests that severe anaphylaxis is another condition for which microalbuminuria is a sensitive monitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Numerous clinical studies have demonstrated the association of urine albumin with the severity of inflammatory insults such as trauma (17), ischemia reperfusion injury (18,19), pancreatitis (20), meningitis (21), endothelial dysfunction (22), and anaphylactic shock (23). Urine albumin correlated with disease activity in patients with inflammatory bowel disease and with circulating tumor necrosis factor-␣ concentrations (24,25).…”
mentioning
confidence: 99%
“…Numerous clinical studies have demonstrated the association of urine albumin with the severity of inflammatory insults such as trauma (17), ischemia reperfusion injury (18,19), pancreatitis (20), meningitis (21), endothelial dysfunction (22), and anaphylactic shock (23). Urine albumin correlated with disease activity in patients with inflammatory bowel disease and with circulating tumor necrosis factor-␣ concentrations (24,25).…”
mentioning
confidence: 99%
“…Temporary proteinuria is present in many acute conditions (1)(2)(3)(4), can be induced by strenuous exercise (5 ), and involves many specific proteins, including albumin and orosomucoid (␣ 1 -acid glycoprotein) (1,5,6 ). Excess excretion of urinary proteins in the absence of renal disease, so-called functional proteinuria (7 ), is a common occurrence, but the pathophysiologic mechanisms responsible for this type of proteinuria are not known.…”
mentioning
confidence: 99%
“…A wide body of recent work has investigated the utility of microalbuminuria measurements as an indicator of the severity of trauma and critical illness [5][6][7][8][9][10][11][12][13][14][15]. Microalbuminuria has been shown to rise within 30 minutes of inflammatory and traumatic stimuli [5,20,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In the acute setting, microalbuminuria has been shown to correlate with the severity of a number of insults including surgery [5], trauma [6][7][8], anaphylaxis [9], acute pancreatitis [10], myocardial infarction [11], meningitis [12], and sepsis [13][14][15]. More importantly, microalbuminuria measurements have shown some predictive value in terms of requirements for organ support and survival in a heterogeneous group of critically unwell patients including those with burn injuries [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%